Probing anomalous couplings using di-Higgs production in electron–proton collisions - Kumar, M.; Ruan, X.; Islam, R.; Klein, M.; Klein, U.; Mellado, B.; Cornell, A.S. (Elsevier, 2017)
A proposed high energy Future Circular Hadron-Electron Collider would provide sufficient energy in a clean environment to probe di-Higgs production. Using this channel we show that the azimuthal angle correlation between the missing transverse energy and the forward jet is a very good probe for the non-standard hhh and hhWW couplings. We give the exclusion limits on these couplings as a function of integrated luminosity at a 95% C.L. using the fiducial cross sections. With appropriate error fitting methodology we find that the Higgs boson self coupling could be measured to be g(hhh)((1)) = 1.00(-0.17(0.12))(+0.24(0.14)) of its expected Standard Model value at root s = 3.5(5.0) TeV for an ultimate 10 ab(-1) of integrated luminosity.
Keywords: Higgs boson; Extensions of Higgs sector; Particle production; ATLAS DETECTOR; PAIR PRODUCTION; 8 TEV; BOSON; SEARCH; PARITY; SPIN; MASS; LHC